Literature Review: Effect of Interprofessional Collaboration Implementation of Patient Services - Dewi Purnasiwi; Ikhlas M Jenie (Universitas Airlangga, 2021)
Introduction: At present progress in the health, the sector requires health workers to provide professional services. The patient's problem is also increasingly complex. Health workers are required to work in an integrated manner, therefore good collaboration and collaboration between healthcare professionals is needed in realizing patient satisfaction. Health services in hospitals are carried out by various health professionals. Effective interprofessional collaboration practices are key to providing health services. The management of the patient's health and all actions must be patient-focused. The model of providing care with interprofessional collaboration is very important so that all services are coordinated and there is good communication between caregivers. This study aims to find out about the effect of implementing interprofessional collaboration on patients. Methods: This research is a literature review. The research source was taken from several databases, with the keywords